Outside the library: Early career researchers and use of alternative information sources in pandemic times - Herman, Eti; Nicholas, David; Clark, David; Boukacem-Zeghmouri, Cherifa; Rodriguez-Bravo, Blanca; Abrizah, Abdullah; Sims, David; Watkinson, Anthony; Xu, Jie; Serbina, Galina; Świgon, Marzena; Jamali, Hamid R.; et al. (Learned publishing)
Presents findings from a study into the attitudes and practices of pandemic-era early career researchers (ECRs) in regard to obtaining access to the formally published scholarly literature, which focused on alternative providers, notably ResearchGate and Sci-Hub. The study is a part of the Harbingers project that has been exploring the work lives and scholarly communication practices of ECRs in pre-pandemic times and during the pandemic, and utilizes data from two rounds of interviews with around 170 ECRs from the sciences and social sciences in eight countries. Findings show that alternative providers, as represented by ResearchGate and Sci-Hub, have become established and appear to be gaining ground. However, there are considerable country- and discipline-associated differences. ECRs' country-specific level of usage of the alternative providers is partly traceable to the adequacy of library provisions, although there are other factors at play in shaping ECRs' attitudes and practices, most notably convenience and time saving, as well as the fact that these platforms have become embedded in the scholarly dashboard. There is a dearth of evidence of the impact of the pandemic on ECRs' ways of obtaining scholarly papers.